2003
DOI: 10.1136/pmj.79.932.329
|View full text |Cite
|
Sign up to set email alerts
|

Primary care referral protocol for wrist ganglia

Abstract: The paper summarises current knowledge on ganglia of the wrist including the views of patients and doctors. The efficacy of available treatment options are discussed. Summary points are derived from the available knowledge with a referral protocol from primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
0
17
0
6
Order By: Relevance
“…19 The incidence of ganglions is 43 per 100,000 in women and 25 per 100,000 in men and, according to some authors, a further upward trend is observed -55 per 100,000 of the population per year. 3,12,14 The mean age of the patients included in our study was 41.3 ± 16.9 years and the median age was 39.5 years. These numbers were undoubtedly influenced by the fact that mainly adult patients are admitted to our ward and pediatric patients only sporadically.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19 The incidence of ganglions is 43 per 100,000 in women and 25 per 100,000 in men and, according to some authors, a further upward trend is observed -55 per 100,000 of the population per year. 3,12,14 The mean age of the patients included in our study was 41.3 ± 16.9 years and the median age was 39.5 years. These numbers were undoubtedly influenced by the fact that mainly adult patients are admitted to our ward and pediatric patients only sporadically.…”
Section: Discussionmentioning
confidence: 99%
“…14 In clinical practice, ganglions manifest almost solely as solitary (although sometimes multilocular) tumors, and multiple lesions located in one or more areas of the body are rare. 3 Dermon et al removed a total number of 124 wrist ganglions in 119 patients, out of which dorsal wrist Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations